Impacto da localização de geração distribuída nos dispositivos de proteção de um sistema elétrico - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work has the objective to find the best localization for a distributed generation in an electric power distribution system, through a set of simulated scenarios, as a function of protection devices present in the system. The electrical power test system has 80 bus, consisting of a distribution feeder located in the northwestern region of Rio Grande do Sul, feeds 6256 consumers predominantly residential, the system and distributed generation are modelled and simulated in the Alternative Transient Program (ATP), using real data. The results obtained from the simulations of three different GD insertion scenarios show that the case where GD is inserted closer to the substation is more interesting economically. It is concluded that the simulations are consistent with the bibliography studied,where a connection of distributed generators increases the short-circuit levels throughout the distribution system, making it difficult to coordinate the protection systems, being influenced by the factor of insertion location of distributed generator.
Keywords: Engenharia; Engenharia de energias renováveis; Energias renováveis; Sistema elétrico de potência; Sistema de distribuição de energia elétrica; Geração distribuída; CNPQ::ENGENHARIAS